Look Ma Bell-No Hands! VoiceXML, X+V and the mobile device. - Wilson, Les
The emerging world without wires has fostered a growing number of small and mobile devices (everything from PDAs to smart phones) capable of accessing data and running applications. The trouble is, while devices are getting smaller, human hands and fingers are not.